The General Elections in Kenya, 2007 - Lafargue, Jerôme (Book collections on Project MUSE., 2009)
The 2007 general elections in Kenya led to major unrest. The aim of this book is to examine and analyse the events that set the country on fire for several weeks. The situation has largely stabilised since April 2008, when the articles collected in this book were first individually published. Some political information has been updated post April 2008. The coalition government took shape with Mwai Kibaki remaining President while Raila Odinga became the Prime Minister. The country however remains in suspense, as do the donors who had made it possible for Kenya to restore a semblance of peace. But to what point will they be interested in investing in the country and to protect their place in it? The collection comprises a translation of a special issue of Les Cahiers d'Afrique de l'Est, no. 37, the journal of the Institut Fran?ais de Recherche en Afrique (IFRA) and a collection of articles from Politique Africaine, no. 109. Whilst the tone of the book is not highly optimistic, the thrust is not intended to dampen the unanimous sense of hope in the country that the political and social situation will once more be more than just tolerable.